Remembering the Future : The Experience of Time in Jewish and Christian Liturgy - O'Donnell, Emma (Book collections on Project MUSE., 2015)
Common to both Judaism and Christianity is a heightened engagement with time within liturgical practice, in which collective religious memory and anticipation come together to create a unique sense of time. Exploring the nebulous realms of religious experience and the sense of time, Remembering the Future charts the ways that the experience of time is shaped by the traditions of Judaism and Christianity and experienced within their ritual practices. Through comparative explorations of traditional Jewish and Christian understandings of time, contemporary oral testimonies, and discussions of the work of select twentieth-century Jewish and Christian thinkers, this book maps the temporal landscapes of the religious imagination. Maintaining that the sense of time is integral to Jewish and Christian religious experience, Remembering the Future makes a notable contribution to interreligious studies and liturgical studies. It sheds light on essential aspects of religious experience and finds that the intimacy of the experience of time grants it the capacity to communicate across religious boundaries, subtly transgressing obstacles to interreligious understanding.